A computable general equilibrium modeling of the economic effects of reducing non-tariff measures in the Malaysian food sector / Yew Siew Hoon - Yew , Siew Hoon (2020)
The Malaysian food processing sector is highly regulated with non-tariff measures (NTMs), and particularly with standard NTMs applied to imports. Though these measures are used for legitimate reasons such as health and safety, some appear to have been instituted for political reasons and serve as “hidden” barriers to trade, given this sector is highly import intensive. This sector is therefore considered to be over regulated and it is argued that a reduction of restrictive NTMs and non-tariff barriers (NTBs) is needed to facilitate trade. Since NTMs, in general, are opaque and less transparent relative to tariffs, they pose a significant challenge to assess their direct and indirect effects on the economy. There is an ongoing effort in contemporary economic literature to provide improved theoretical methodologies, and empirical studies to better measure the actual impact of NTMs. This study contributes to the empirical literature in the following manner. First, it provides a quantitative assessment of the economic impacts of the reduction of NTMs in the food processing sector of Malaysia, by means of a disaggregated sectoral analysis. Such a methodology is used given that the Malaysian food industry is highly heterogeneous in terms of its trade intensity, labour usage and wage levels. Second, the indirect effects of a reduction in NTMs on employment are revealed when comparing local and foreign labour. In this context it is noted that the Malaysian food industry is labour intensive and dominated by small and medium-sized firms. The study estimates the production, trade, labour market (employment, wages and wage inequality) and welfare effects, which follow from a reduction of NTMs in 11 sub-sectors of the food processing industry. This empirical analysis uses the computable general equilibrium (CGE) model to simulate the impact of a reduction of NTMs based on three scenarios. They include a baseline scenario with no changes in NTMs, a 10 percent and a 50 percent reduction in NTMs, which are introduced as exogenous shocks into the model. The calibration based on the data is generated from the Social Accounting Matrix (SAM) of Malaysia. The core findings of the study are as follows. First, the change in production and trade following NTM cuts are substantial, especially in the long-run. The sub-sectors that are highly dependent on imported inputs in their production, benefit the most, as they are able to gain access to cheaper imported inputs since business compliance costs are reduced with reductions in NTMs. Second, NTM reductions incur positive indirect effects on employment, with employment gains most notable in the export oriented sub-sectors. Interestingly, the dependency on unskilled labour (both local and foreign) increases with the NTM cuts, but the wages for this group decreases. Third, the overall welfare in the economy increases, albeit minimally, with NTM cuts. The study supports a reduction of NTMs in the food processing industry to enhance production, trade and welfare of the economy. This, in turn, underlines the presence of existing restrictive NTMs or NTBs in this industry. To reduce the incidence of restrictive measures, policymakers need to address the design and method of adoption of NTMs across the food industry’s sub-sectors. Policymakers may also need to regulate unskilled foreign labour to ensure that an upgrading of the industry is not compromised following its expansion.